PENGEMBANGAN INDUSTRI KERAJINAN DAN MEBEL ROTAN BERBASIS KEARIFAN LOKAL - Agung Purnomo; Sumarno Sumarno; Deny Dwi Hartomo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Indonesia’s natural and cultural wealth represents an extraordinary gift that is not compared to others in the world, for example rattan and batik. Batik and rattan as Indonesia’s natural and cultural wealth become the base to increase the competitiveness and productivity of the rattan furniture industry in Sukoharjo Regency. The efforts of the improvement are in case of export-oriented industries, especially Surya Rotan and Agung Rejeki Furniture. Product creation and various things related to the market and production are also become a concern in this applied research. This research uses TDA (Total Design Activity) approach. Six aspects in TDA approach include market, specification, concept design, detailed design, manufacture and sales. The activities undertaken include product design, design of appropriate technology, product protection through industrial design rights, exhibitions, and training and production assistance. Rattan as a superior raw material, the ability to process Indonesian rattan, and finishing rattan products with batik is then used as the base of furniture product design. The furniture product design of rattan and rattan finishing become the base for creating furniture products of chairs, tables, and even handicraft products.